Improving library service quality and collection management at Politeknik Pariwisata NHI Bandung - Lina Rismawati (Universitas Pendidikan Indonesia, 2026)
University libraries are crucial for the implementation of the Tri Dharma of Higher Education. Complex user needs demand efficient services and reliable collection management. This community service program took place at the NHI Bandung Tourism Polytechnic Library over 40 working days, using a participatory approach and fostering close collaboration between the team and librarians. Activities focused on supporting thesis/final project (TA/PA) services, digital and print collection processing, archive handling, and security checks. Results showed a more organized TA/PA workflow and controlled access to TA/PA collections over the past 6 years (2019–2024). Digital discovery improved with the addition of Emerald e-journal metadata to the library website, and new printed books were thoroughly processed (classification, cataloging, labeling, and shelving). Collection governance was strengthened through the weeding of 612 items and a physical inventory of 14,479 items, supported by sensory checks of reference materials. These results demonstrate that targeted operational support can improve service efficiency, data accuracy, and collection relevance; Libraries must standardize workflows, schedule regular weeding/inventories, and modernize supporting equipment. The next step is to measure user satisfaction and match the physical collection with the integrated catalog. Abstrak Perpustakaan perguruan tinggi sangat penting dalam pelaksanaan Tri Dharma Perguruan Tinggi. Kebutuhan pengguna yang kompleks menuntut layanan yang efisien serta tata kelola koleksi yang andal. Program pengabdian masyarakat ini berlangsung di Perpustakaan Politeknik Pariwisata NHI Bandung selama 40 hari kerja, dengan pendekatan partisipatif dan kolaborasi yang erat antara tim dan pustakawan. Kegiatan difokuskan pada dukungan layanan tesis/proyek akhir (TA/PA), pengolahan koleksi digital dan cetak, penanganan arsip, serta pemeriksaan keamanan. Hasil menunjukkan alur kerja TA/PA yang lebih teratur serta akses yang terkontrol terhadap koleksi TA/PA selama periode 6 tahun terakhir (2019–2024). Penemuan digital meningkat melalui entri metadata jurnal elektronik Emerald ke situs web perpustakaan, dan buku cetak baru diproses secara menyeluruh (klasifikasi, katalogisasi, pelabelan, dan penataan rak). Tata kelola koleksi diperkuat melalui penyiangan 612 item dan inventarisasi fisik sebanyak 14.479 item, didukung oleh pengecekan sensorik terhadap bahan referensi. Hasil ini menunjukkan bahwa dukungan operasional yang tepat sasaran dapat meningkatkan efisiensi layanan, akurasi data, dan relevansi koleksi; perpustakaan harus menstandarisasi alur kerja, menjadwalkan penyiangan/inventarisasi secara rutin, serta memodernisasi peralatan pendukung. Pekerjaan selanjutnya adalah mengukur kepuasan pengguna dan mencocokkan koleksi fisik dengan katalog yang terintegrasi. Kata Kunci: inventarisasi; manajemen koleksi; optimalisasi layanan; perpustakaan perguruan tinggi